1997
DOI: 10.1046/j.1365-2591.1997.00086.x
|View full text |Cite
|
Sign up to set email alerts
|

Sealing properties of a new epoxy resin‐based root‐canal sealer

Abstract: In this study a new epoxy-resin-based endodontic sealer, AH Plus, was tested in vitro for apical leakage. The conventional sealer AH26, for which information is already available, was used as the control. The root canals of 72 single-rooted teeth were prepared biomechanically using a stepback technique before lateral condensation of gutta-percha with one of the two sealers. Teeth were immersed in 5% methylene blue dye for 2, 4 or 10 days. The roots were split longitudinally so that the extent of dye penetratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
20
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 8 publications
3
20
0
Order By: Relevance
“…23 Several studies concerning root canal sealers classify AH Plus sealer as the product with the lowest apical marginal dye index. 4,[14][15][16]24,25 However, as found in this and other studies (e.g., Onay et al), 26 Figure 1 -SEM images of the dentin surface without laser irradiation (A), showing a clean wall free of smear layer and open dentin tubules; after diode laser irradiation (B), melting of the dentin surface can be noted, along with a few dentin tubules, most of them occluded.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…23 Several studies concerning root canal sealers classify AH Plus sealer as the product with the lowest apical marginal dye index. 4,[14][15][16]24,25 However, as found in this and other studies (e.g., Onay et al), 26 Figure 1 -SEM images of the dentin surface without laser irradiation (A), showing a clean wall free of smear layer and open dentin tubules; after diode laser irradiation (B), melting of the dentin surface can be noted, along with a few dentin tubules, most of them occluded.…”
Section: Discussionsupporting
confidence: 58%
“…3,4,[6][7][8][9][10][11][12] There are several studies about materials and root canal filling techniques that aim to achieve apical sealing of teeth. [13][14][15][16][17] Currently, studies with Epiphany (Pentron Clinical, Orange, USA) and RealSeal (Sybron Endo, Redmond, USA), both methacrylate-based resin sealers, have shown promising results in comparison with other base sealers. 1,18,19 However, it is not well-known if the combined association of intracanal Declaration of Interests: The authors certify that they have no commercial or associative interest that represents a conflict of interest in connection with the manuscript.…”
Section: Introductionmentioning
confidence: 99%
“…One possible explanation is that the silicone oils used in AH-Plus™ may prevent complete wetting of the canal walls by the material. 144 The present results also revealed differences between the two MTA cements. This point is more of scientific rather than clinical importance, as MTA materials would not normally be used for the bulk obturation of a canal, despite their common use for perforation repairs.…”
Section: Discussionsupporting
confidence: 54%
“…It is believed that the AH plus sealer did not adapt well to dentin walls because of the hydrophobic properties of epoxy resins. 23 And a study reported that all the specimens filled with AH plus sealer leaked within 13 days. This could be because of shrinkage of this epoxy type sealer during setting.…”
Section: Discussionmentioning
confidence: 99%